Changes in Religiosity of Volyn Czechs - Nešporová, Olga (Lidé města, 2005)
Volyn Czechs compose a group that has been afforded significant attention by both scientific researchers, as well as by regular citizens. However, despite this interest the topic of religiosity has been mostly neglected and was totally sidetracked away from major interest of researchers who are interested in this group during the post-emigration period when especially the gradual integration of repatriates into the majority society was investigated.